GRAMMATICAL ERRORS IN ESP STUDENTS’ PRESENTATION ACROSS PROFICIENCY LEVELS - Ruminar, Hafida (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2018)
This study analyzes the grammatical errors across proficiency levels. The samples were collected from the second semester of Agriculture students’ oral presentation in ESP class. They were grouped into high and low proficient students by using TOEFL test. The errors in their speech were classified by using surface structure taxonomy namely misformation, misorder, addition, omission, blends, and miscellaneous. Findings indicate that misformation is the dominant error produced by both levels of proficiency. It is followed by omission, addition, miscellaneous, misorder, and blends.